Implementasi sila kedua dan kelima Pancasila dalam penegakan HAM terhadap korban kekerasan seksual di Indonesia - Saluka, Fathma Ilma Silvi (Maliki Interdisciplinary Journal, 2025)
Sexual violence is one of the most serious forms of human rights violations in Indonesia. Although Law Number 12 of 2022 on the Crime of Sexual Violence (UU TPKS) has been enacted, the implementation of protection for victims of sexual violence still faces various structural, cultural, and institutional obstacles. Pancasila, as the foundation of the state, plays a role as a source of moral values, meaning that it serves as a guideline for the way of life of Indonesian society. This shows that every action and behavior of the Indonesian people must be in accordance with the values of Pancasila. This journal explains the relevance of the second principle of Pancasila, namely “Just and Civilized Humanity,” and the fifth principle of Pancasila, namely “Social Justice for All the People of Indonesia,” in the practice of protecting victims of sexual violence. Using a literature analysis method, this article examines recent research, human rights institution data, and relevant policy documents. The results of the analysis indicate the persistence of gaps between regulation and practice, marked by revictimization, discrimination, and unequal access to legal and psychosocial services. The article also compares victim protection practices in other countries as an evaluation material to improve policies in Indonesia. Based on these findings, this study recommends Pancasila-based strategies to strengthen the protection and recovery of victims of sexual violence in Indonesia.